Description of two new Proceroecia species (Ostracoda: Halocyprididae) from neritic waters off South Korea with an insight into the morphological and molecular diversity of the genus - Choi, Eunha; Karanovic, Ivana; Lee, Wonchoel; Angel, Martin V. (Zootaxa, 2020)
Two new planktonic ostracods of the genus Proceroecia Kock, 1992, P. hwanghaensis sp. nov. and P. joseondonghaensis sp. nov., collected from neritic waters off the south coast of South Korea are described. Morphologically, they are similar to P. microprocera (Angel, 1971), the type species of the genus, but show several clear morphological differences, most prominent being the shape of the male endopodite on the second antenna and the presence of a sensilla on the coxale of the fifth limb. The two new species have subtle differences, such as the length of the frontal organ, number of spines on the comb-like e-seta on the first antenna in males, number of spinules on the b-seta on the second antenna in females, etc. Sequences derived from partial mitochondrial cytochrome oxidase c subunit 1 (mtCOI) for these novel species have been compared with sequences available for other Proceroecia species on GenBank, including P. microprocera. These comparisons suggest that both new species are distinct taxa. They also indicate that one set of sequences on GeneBank previously attributed to P. microprocera and derived from material collected from Chinese waters, belong to P. hwanghaensis, and that another set of sequences of an unidentified Proceroecia species from the South China Sea can be attributable to P. joseondonghaensis. Hence, these new species occur widely in the neritic waters of East Asia. The present study increases the number of the known Proceroecia species to nine, and the numbers of halocyprid ostracod species recorded from Korean waters to six.